2015
DOI: 10.1007/s13277-014-2969-7
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 associates with the malignant status and poor prognosis in glioma

Abstract: The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a bona fide long noncoding RNA (lncRNA). LncRNA MALAT1 was discovered as a prognostic factor for lung cancer metastasis but also has been linked to several other human tumor entities. However, little is known about the role of lncRNA MALAT1 in glioma patients. The aim of this study was to identify the role of lncRNA MALAT1 in the pathogenesis of glioma; we analyzed the relationship of lncRNA MALAT1 expression with clinicopathological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 31 publications
5
116
1
Order By: Relevance
“…TUG1-knockdown has been associated with cell cycle arrest in G 0 /G 1 phase (14). Glioma has been reported to be the most common type of primary cerebral tumor (1). Owing to the highly invasive growth pattern of the disease and the frequent occurrence of resistance to chemotherapy, patients with glioma often succumb to the disease (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TUG1-knockdown has been associated with cell cycle arrest in G 0 /G 1 phase (14). Glioma has been reported to be the most common type of primary cerebral tumor (1). Owing to the highly invasive growth pattern of the disease and the frequent occurrence of resistance to chemotherapy, patients with glioma often succumb to the disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…Glioma is the most common brain tumor in humans, and is associated with various genetic disorders (1). Patient with glioma continue to have extremely poor prognoses, despite recent advances in chemotherapy, radiotherapy and surgery (1); the median survival in patients with glioblastoma multiforme (World Health Organization, grade IV) may be only 12-15 months (2).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-nine potentially relevant articles were selected for full-text review (Figure1). Finally, 12 primary studies, including 958 patients, met the inclusion criteria (Ji et al, 2003;Lai et al, 2012;Cho et al, 2014;Liu et al, 2014;Okugawa et al, 2014;Zheng et al, 2014;Dong et al, 2015;Hirata et al, 2015;Li et al, 2015;Ma et al, 2015;Pang et al, 2015;Zhang et al, 2015). Details regarding the participants of these studies are summarized in Table 1.…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…Therefore, expression of this lncRNA can be seen to be correlated with the clinical features and prognosis of certain cancers. Nevertheless, recent studies related to its role in carcinogenesis have generated conflicting results (Okugawa et al, 2014;Zheng et al, 2014;Ma et al, 2015;Zhang et al, 2015). Therefore, in this meta-analysis we endeavored to evaluate the effect of MALAT1 expression on clinical pathological features and prognosis in various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that MALAT-1 can promote cancer cell proliferation and metastasis by activating the ERK/MAPK pathway and interacting with hnRNP in cell cycle regulation (Yang et al, 2013;Wu et al, 2014). Moreover, research has demonstrated that high MALAT-1 expression can serve as an important prognostic element in other cancers such as pancreatic and colorectal malignancies and gliomas (Liu et al, 2014;Zheng et al, 2014;Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%